The cuckoo's egg tracking a spy through the maze of computer espionage - Stoll, Clifford
This is the true story of how a systems manager at Lawrence Berkeley Lab singlehandedly tracked down and helped capture a computer hacker who had been breaking into U.S. computer systems and stealing sensitive military and security information. Cliff Stoll was an astronomer turned systems manager at Lawrence Berkeley Lab when a 75-cent accounting error alerted him to the presence of an unauthorized user on his system. The hacker's code name was "Hunter"--A mystery invader hiding inside a twisting electronic labyrinth, breaking into U.S. computer systems and stealing sensitive military and security information. Stoll began a one-man hunt of his own, spying on the spy -- and plunged into an incredible international probe that finally gained the attention of top U.S. counterintelligence agents. The Cuckoo's Egg is his wild and suspenseful true story -- a year of deception, broken codes, satellites, missile bases, and the ultimate sting operation -- and how one ingenious American trapped a spy ring paid in cash and cocaine, and reporting to the KGB